Modeling and monitoring riparian buffer zones using LiDAR data in South Carolina - Akturk, Emre; Post, Christopher; Mikhailova, Elena A (Springer Science and Business Media LLC, 2020)
Functional riparian areas protect water quality and conserve aquatic systems, plants, and wildlife. Laser-based remote sensing technology offers a high-resolution approach to both characterize and document changes in riparian buffer zones (RBZs). The objectives of this study were to demonstrate a rapid method and model to calculate riparian buffer widths on both sides of a stream using a LiDAR-derived slope variable, to classify riparian buffers and determine their quality, and to evaluate the appropriateness of using LiDAR in riparian buffer assessment. For this purpose, RBZs were delineated for Hunnicutt and King Creek, which are located in Oconee and Pickens counties, in South Carolina. Results show that LiDAR was effective in delineating required riparian buffer widths based on the topography slope of upstream areas, and in calculating the ratio of tree cover. This LiDAR-based assessment methodology could be applied to a wide-range of environments.
Keywords: Rivers; South Carolina; Remote Sensing Technology; Ecosystem; Environmental Monitoring; Trees; 15. Life on land; 6. Clean water